Compass systems - Chernetsov, Nikita (Journal of Comparative Physiology, 2017)
Three compass systems based on global cues known to exist in migrating birds are reviewed. Two of these systems are based on celestial cues, a time-dependent sun compass and time-independent, i.e. not involving the internal clock, star compass. The third system is the magnetic compass, based on a separate sensory modality, which currently attracts much attention from behavioural ecologists, physiologists and physicists. The complex pattern of hierarchy and interactions between these compass systems is briefly discussed. It is argued that rules of integration of information from different compass cues are likely dependent on ecological and geographic conditions the birds are facing during their journey, so it is likely that no single set of rules is shared by all migrating birds.